Khalifah Mu’awiyah bin Abu Sufyan : Peletak Dasar Pemerintahan Islam Monarki 661 - 680 M - Abdul Aziz Nashiruddin; andi suwirta (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2020)
This study entitled “Mu’awiyah bin Abu Sufyan who became the pioneer of Monarchical Islamic government in the period 661-680 AD”. The issue background was because Mu’awiyah bin Abu Sufyan became the prominent pioneer in changing the Islamic government to a monarchic system that had never been applied in the Islamic Caliphate before. The main problem raised is “Why did Mu’awiyah change the Islamic caliphate to a monarchical system?” The method used is a historical research method by conducting four steps of research namely heuristics, criticism, interpretation, and historiography. The results of the study can be explained including before there was a change in the Islamic government system to the monarchy. During the reign of Khulafaur Rashidun, the government system adopted by the Islamic caliphate was based on democracy. Mu’awiyah as the caliph subsequently faced many problems, from disputes between companion of prophet Muhammad SAW to wars that occurred due to internal problems, and decided to change the system of government to a monarchy. In the early days of Mu’awiyah’s leadership, he formed a governmental order to rebuild the Islamic caliphate from the destruction of internal conflict. Mu’awiyah’s leadership was more or less twenty years, in contrast to the previous caliphs Mu’awiyah handed over the power of the caliphate to Yazid bin Mu’awiyah. Determination of the crown prince impacted the caliphates thereafter, which changed the caliphate of Islam with a democratic system of monarchy.